Advancements and Challenges in Drone Technology: A Comprehensive Review - Agrawal, P. S.; Jawarkar, P. S.; Dhakate, K. M.; Parthani, K. M.; Agnihotri, A. S. (2024 4th International Conference on Pervasive Computing and Social Networking (ICPCSN), 2024)
This research study analyzes the dynamic nature of drone technology, exploring its multifaceted applications, societal impacts, and the evolving challenges in its deployment. The integration of Unmanned Aerial Vehicles (UAVs) in various sectors, particularly in the fields of precision agriculture, cinematography, and geospatial mapping, is examined for its transformative potential. The paper highlights the revolutionary role of drones in addressing challenges such as search and rescue operations, natural disaster management, and providing virtual tourism experiences. Notably, the integration of Geographic Information System (GIS) technology and autonomous capabilities in drones is discussed in the context of cinematography and indoor inspections, emphasizing the need for a balance between technological innovation and ethical considerations. The comprehensive analysis includes insights into the security threat landscape associated with Augmented Reality (AR) drones, underlining the importance of conducting thorough threat analyses to ensure the safe operation of remotely piloted aircraft systems. Researchers have addressed concerns related to cyber threats, categorizing various aspects of the UAV threat landscape and developing classification approaches based on connections and nodes within flying ad-hoc networks (FANETs) and the Internet of Drones (IoD) infrastructure.